Emerging therapeutic role of gut microbial extracellular vesicles in neurological disorders - Sun, Bowen; Sawant, Harshal; Borthakur, Alip; Bihl, Ji Chen (Frontiers in Neuroscience, 2023)
Extracellular vesicles (EVs) serve as cell-to-cell and inter-organ communicators by conveying proteins and nucleic acids with regulatory functions. Emerging evidence shows that gut microbial-released EVs play a pivotal role in the gut-brain axis, bidirectional communication, and crosstalk between the gut and the brain. Increasing pre-clinical and clinical evidence suggests that gut bacteria-released EVs are capable of eliciting distinct signaling to the brain with the ability to cross the blood–brain barrier, exerting regulatory function on brain cells such as neurons, astrocytes, and microglia, via their abundant and diversified protein and nucleic acid cargo. Conversely, EVs derived from certain species of bacteria, particularly from gut commensals with probiotic properties, have recently been shown to confer distinct therapeutic effects on various neurological disorders. Thus, gut bacterial EVs may be both a cause of and therapy for neuropathological complications. This review marshals the basic, clinical, and translational studies that significantly contributed to our up-to-date knowledge of the therapeutic potential of gut microbial-derived EVs in treating neurological disorders, including strokes, Alzheimer’s and Parkinson’s disease, and dementia. The review also discusses the newer insights in recent studies focused on developing superior therapeutic microbial EVs via genetic manipulation and/or dietary intervention.